Patients with severe mental illness and their carers' expectations for GPs' communication skills: a qualitative approach in Spain. - Ramos-Ruiz, Juan Andrés; Pérez-Milena, Alejandro; Noguera-Cuenca, Carmen; Rodríguez-Bayón, Antonina; Ruiz-Díaz, Beatriz (BJGP Open, 2024)
Background: Effective communication with GPs (General Practitioners) enables higher rates of patient satisfaction and adherence to treatment plans. People with severe mental illness (SMI) and their caregivers present unique characteristics that present difficulties in the GP-carer-patient communication process. Aim: To explore the expectations of patients with SMI and their caregivers regarding GPs' communication skills in primary care consultations. Design & setting: Face-to-face interviews, using focus group methodology, which were undertaken in southern Spain. Method: Forty-two participants took part in 21 paired semi-structured interviews with an average duration of 19±7.2 minutes. Information was audio-recorded and transcribed verbatim. Qualitative content analysis was undertaken, obtaining a codification in categories by means of triangulation. Results: Four themes emerged from the analysis. Theme 1 was interviewer communication characteristics. The ability of GPs to use a language that was colloquial and adapted to each person was perceived as a determinant of the quality of care provided. An empathetic attitude, low reactivity, and efficient time management were the most valued communication skills. Theme 2 was telemedicine: telephone consultation and video consultation. The telephone consultation was perceived as a useful tool to care for people with SMI. Video consultation was valued as a requirement in isolated rural areas. Theme 3 was the role of the caregiver during the clinical interview. The caregiver was considered by the patients as an ally who improves the clinical interview. Theme 4 was the perceived barriers and facilitators during the clinical interview. The continuity of care, defined by a low turnover of GPs, determined the quality perceived by those who required care. Conclusion: Themes emerging from this study have suggested that people with SMI require an inclusive, collaborative, and personalised approach in the care they receive from the public health system. Improved communication between GPs and patients with SMI is an essential requirement for quality medical care.